Microglia P2Y13 Receptors Prevent Astrocyte Proliferation Mediated by P2Y1 Receptors - Quintas, Clara; Vale, Nuno; Gonçalves, Jorge; Queiroz, Glória (Frontiers in Pharmacology, 2018)
Cerebral inflammation is a common feature of several neurodegenerative diseases that requires a fine interplay between astrocytes and microglia to acquire appropriate phenotypes for an efficient response to neuronal damage. During brain inflammation, ATP is massively released into the extracellular medium and converted into ADP. Both nucleotides acting on P2 receptors, modulate astrogliosis through mechanisms involving microglia-astrocytes communication. In previous studies, primary cultures of astrocytes and co-cultures of astrocytes and microglia were used to investigate the influence of microglia on astroglial proliferation induced by ADPbetaS, a stable ADP analogue. In astrocyte cultures, ADPbetaS increased cell proliferation through activation of P2Y1 and P2Y12 receptors, an effect abolished in co-cultures (of astrocytes with ~12.5% microglia). The possibility that the loss of the ADPbetaS-mediated effect could have been caused by a microglia-induced degradation of ADPbetaS or by a preferential microglial localization of P2Y1 or P2Y12 receptors was excluded. Since ADPbetaS also activates P2Y13 receptors, the contribution of microglial P2Y13 receptors to prevent the proliferative effect of ADPbetaS in co-cultures was investigated. The results obtained indicate that P2Y13 receptors are low expressed in astrocytes and mainly expressed in microglia. Furthermore, in co-cultures, ADPbetaS induced astroglial proliferation in the presence of the selective P2Y13 antagonist MRS2211 (3 microM) and of the selective P2Y12 antagonist AR-C66096 (0.1 microM), suggesting that activation of microglial P2Y12 and P2Y13 receptors may induce the release of messengers that inhibit astroglial proliferation mediated by P2Y1,12 receptors. In this microglia-astrocyte paracrine communication, P2Y12 receptors exert opposite effects in astroglial proliferation as a result of its cellular localization: cooperating in astrocytes with P2Y1 receptors to directly stimulate proliferation and in microglia with P2Y13 receptors to prevent proliferation. IL-1beta also attenuated the proliferative effect of ADPbetaS in astrocyte cultures. However, in co-cultures, the anti-IL-1beta antibody was unable to recover the ADPbetaS-proliferative effect, an effect that was achieved by the anti-IL-1alpha and anti-TNF-alpha antibodies. It is concluded that microglia control the P2Y1,12 receptor-mediated astroglial proliferation through a P2Y12,13 receptor-mediated mechanism alternative to the IL-1beta suppressive pathway that may involve the contribuition of the cytokines IL-1alpha and TNF-alpha.